Application of Aroma for Edible-Nest Swiftlets Attraction - C. M. A., Che Mohd; Saiful Nizam, Tajuddin (2014)
Based on sharing of experiences with trusted swiftlet farming consultants and scientific approach, it is concluded that birdhouse aroma are divided into top and floor aroma. Formulated from natural plant, top aroma known as attractant aroma served to lure swiftlets especiall y young couple to enter the birdhouse. However, additional top aroma known as pheromone aroma also need to be applied on nesting plank to stimulate those birds mate and breed. This aroma is made up of the bird 's nest waste water from cleaning process. In addition, floor aroma that is usually applied on bottom region of birdhouse cannot be neglected as the smell of swiftlet"s guano will convince those birds that the house is safe and were populated by other swiftlets although it i ~ not. The main concern in aroma application is that ranchers need to avoid the wrong practice as swiftlets are sensitive to odour and may not build their nest on nesting plank stained with their guano.